Catalytic Performance of a Class III Old Yellow Enzyme and Its Cysteine Variants - Scholtissek, Anika; Gädke, Eric; Paul, Caroline E.; Westphal, Adrie H.; van Berkel, Willem J. H.; Tischler, Dirk (Frontiers in Microbiology, 2018)
Class III old yellow enzymes (OYEs) contain a conserved cysteine in their active sites. To address the role of this cysteine in OYE-mediated asymmetric synthesis, we have studied the biocatalytic properties of OYERo2a from Rhodococcus opacus 1CP (WT) as well as its engineered variants C25A, C25S and C25G. OYERo2a in its redox oxidized resting state (oxidized form) is irreversibly inactivated by N-methylmaleimide. As anticipated, inactivation does not occur with the Cys variants. Steady-state kinetics with this maleimide substrate revealed that C25S and C25G doubled the turnover frequency (kcat) while showing increased KM values compared to WT, and that C25A performed more similar to WT. Applying the substrate 2-cyclohexen-1-one, the Cys variants were less active and less efficient than WT. OYERo2a and its Cys variants showed different activities with NADPH, the natural reductant. The variants did bind NADPH less well but kcat was significantly increased. The most efficient variant was C25G. Replacement of NADPH with the cost-effective synthetic cofactor 1-benzyl-1,4-dihydronicotinamide (BNAH) drastically changed the catalytic behavior. Again C25G was most active and showed a similar efficiency as WT. Biocatalysis experiments showed that OYERo2a, C25S and C25G converted N-phenyl-2-methylmaleimide equally well (81 – 84%) with an enantiomeric excess (ee) of more than 99% for the R-product. With cyclic ketones, the highest conversion (89%) and ee (>99%) was observed for the reaction of WT with R-carvone. A remarkable poor conversion of cyclic ketones occurred with C25G. In summary, we established that the generation of a cysteine-free enzyme and cofactor optimization allows the development of more robust class III OYEs.